Cash and COVID-19: The effects of lifting containment measures on cash demand and use - Heng Chen; Walter Engert; Kim P. Huynh; Gradon Nicholls; Hui Zhu (Bank of Canada, 2021)
We conduct a follow-up to Chen et al. (2020) and study demand for and use of cash after the containment measures imposed at the beginning of the COVID-19 pandemic were relaxed during the summer of 2020. We find that bank notes in circulation continued to rise in July due to ongoing cash withdrawals and decreased cash deposits in the Bank Note Distribution System. The probability of consumers using cash for payments increased in July compared with April 2020. As well, consumer cash holdings, measured as the median value of cash on hand, returned to August 2019 levels.
Keywords: C; C1; C9; C12; E; E4; O; O5; O5; 330; Bank notes; Central bank research; Coronavirus disease (COVID-19); Digital currencies and fintech; Econometric and statistical methods